Persepsi Masyarakat Terhadap Program Pemberdayaan Masyarakat Binaan Balai Taman Nasional Komodo (Studi Kasus: Kampung Rinca) - Yovita Roukawali Bunga; Marius Yosef Seran; Mappiasse; Muhammad Ikbal Putera (JURNAL AKADEMISI VOKASI, 2024)
The purpose of this research is to evaluate the community empowerment program implemented by the Komodo National Park Center in Rinca Village and understand the level of community satisfaction with the community empowerment program that has been implemented. This research uses quantitative methods in a observation descriptive approach. The research population includes all community groups involved or affected by the empowerment program, while the research sample was taken as many as 55 respondents from the population. The data collection technique used to measure community satisfaction with the empowerment program is a questionnaire. This questionnaire includes 3 indicators on each of 11 statements with a Likert scale of 1 - 5. The results stated that most chose 4 (Agree) in this case it can be stated that they are “satisfied” with the empowerment program implemented, although there are aspects that need to be improved. In summary, this research is useful from a theoretical point of view to further research and more effective program planning for the future and from a practical point of view the results of this study can be used by the Komodo National Park as an evaluation and improvement of the program.